Technical and Economic Analysis of Net Energy Metering for Residential House - T. M. N. T. Mansur; N. H. Baharudin; R. Ali (Institute of Advanced Engineering and Science, 2018)
Renewable Energy Act (RE Act) has been gazetted by the Malaysian Government in 2011 to encourage energy generation from renewable resources. Under Feed-in Tariff (FiT) scheme, solar PV has gained popularity due to its high FiT rates. However, the FiT scheme for solar PV has expired in 2016 and been replaced by the Net Energy Metering (NEM) scheme. The objective of this research work is to technically and economically analyze the solar PV system for a residential house under NEM scheme. The methodology involves gathering solar energy resource information and daily residential load profile, sizing PV array together with grid-connected inverter and then lastly simulation of the design system by using PVsyst software. Based on the results obtained, the amount of energy generated is higher when the capacity of solar PV system is increased. While most of the energy generated is exported to the grid, only up to 25% of load demand is supplied by the solar PV system. From economic aspect, the residential house does not need to pay the electricity bill due to the self-consumed of energy generated and profit gained from excess energy exported to the grid. From the environmental aspect, 2,434 kWh energy generated from renewable resource annually and consumed by the residential load has replaced the fossil fuel based power from grid. This value is equivalent to almost 1.7 tons of CO2 avoidance to the environment.